HUKUM ISLAM TENTANG MINUMAN KERAS Pencegahan dan Penanggulangan Perilaku Minuman Keras di Desa Sidomulyo Kecamatan Dempet Kabupaten Demak - Taufiqin Taufiqin (Program Studi Hukum Keluarga Islam, 2015)
The purpose of this study is to determine how the government of Sidomulyo, Dempet, Demak, along with religious leaders and community leaders unite to implement Islamic law on the prohibition of liquor and the actions taken for prevention and mitigation. The method used is a qualitative research; with data collecting technique uses interview, observation and documentation. Data is analyzed in 6 (six) phases: 1) Processing and preparing the data. 2) Reading the data. 3) Analyzing in more detail by coding data. 4) The process of coding data. 5) Presenting in narrative / qualitative. 6) Interpreting the data. The results showed that the government of Sidomulyo along with religious and community leaders have a good understanding of liquor as much as 20 respondents (46.5%), while 16 (37.2%) and the rest of the respondents want 100 % changes, ie village Sidomulyo clean of liquor, either with precaution or prevention.